UPAYA INDONESIA MENJADIKAN LABUAN BAJO SEBAGAI DESTINASI MICE INTERNASIONAL TAHUN 2023 - Novtasya, Klara; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The implementation of international MICE events provides various benefits for the region or host organizers both from the economic sector and foreign exchange to national branding which can improve the image of the organizers in the international world. This research aims to analyze the strategies and efforts made by the Indonesian government in developing Labuan Bajo as an international MICE (Meetings, Incentives, Conventions, and Exhibitions) destination in 2023. The research method used in this study is descriptive qualitative. The data collection method is collected from analyzing documents such as international and national journals, books, official publications, news, twitter and other relevant sources. The theory used is the theory of national branding to explain the government's efforts to make Labuan Bajo a MICE Destination (Meetings, Incentives, Conventions, and Exhibitions) in 2023 with the level of analysis used is the country. The study showed that the Indonesian government through the Ministry of Tourism and Creative Economy has launched various programs and initiatives to improve the attractiveness and infrastructure of Labuan Bajo. Some of them are the construction of international standard convention facilities, increasing airport capacity, and intensive promotion through various international media and events. In addition, cooperation with various stakeholders, including the private sector and local communities, is a key factor in realizing these goals. Keywords: MICE (Meeting, Incentives, Convention, and Exhibitions), Labuan Bajo, ASEAN Summit, Indonesia